PENERAPAN MODEL PEMBELAJARAN CTL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII-A SMP NEGERI 3 DHARMA CARAKA TELUKDALAM - Yohanna Theresia Venty Fau (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study was to determine the improvement in student learning outcomes when implementing the CTL learning model at SMP Negeri 3 Dharma Caraka Telukdalam. This study is a classroom action research. The subjects of this study were students of class VII-A of SMP Negeri 3 Dharma Caraka Telukdalam. The results of the study obtained that the application of the CTL learning model in class VII-A can improve student learning outcomes where there is an increase from cycle I to cycle II. The percentage of student activity observations in cycle I is in the sufficient category. While student activity in cycle II experienced an increase, namely in the good category. Students' cognitive learning outcomes in cycle I obtained an average of 67.97 with a percentage of completion of 59.38%. In cycle II, student learning outcomes increased with an average of 80.78 with a percentage of completion of 93.75%.